Hot Water Dipping and UV Irradiation of Apples to Control Fruit Rots - Neelam Kumari; J. N. Sharma; Deepika Singh (International Journal of Economic Plants)
The efficacy of hot water dipping and UV irradiation against apple storage rots caused by Alternaria alternata (mouldy core), Trichothecium roseum (pink mould rot), Monilinia fructigena (brown rot), Aspergillus niger (black rot) and Penicillium expansum (blue mould rot) was examined. Artificially inoculated Starking Delicious apples were incubated for 3 min in a water bath heated to specific temperatures in the range of 48 ˚C to 52 ˚C. Storage rots caused by all the five species were significantly reduced at dipping temperature of 48 ˚C. UV irradiation of fruits for 15 min was found most effective in reducing decays caused by all the test fungi. These results suggest possible applications of hot water dipping and UV irradiation of apples at harvest, after short-term cold storage or after the opening of controlled-atmosphere storage rooms in order to reduce decays during subsequent storage periods.